MANAJEMEN PENGEMBANGAN PERPUSTAKAAN DI DINAS PERPUSTAKAAN DAN KEARSIPAN DAERAH KABUPATEN KUANTAN SINGINGI TAHUN 2019 - Jeprinaldi "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Library development management, a practical approach, explains that "Library management is library management based on management theory and principles. The Kuantan Singi District Public Library has not received the accreditation predicate from the Indonesian National Library, and includes 6 districts in Riau Province that have not been accredited. This study aims to determine and analyze library development management and inhibiting factors of development management in the Department of Library and Archives of Kuantan Singingi Regency.This type of research uses qualitative methods with interview data collection techniques, and documentation. The research location is in Kuantan Singingi Regency in the Regional Library and Archives Office of Kuantan Singingi Regency. The types and sources of research data are divided into primary data with purposive informant retrieval techniques and secondary data in the form of supporting data related to library development management.The results showed that the Kuansing Library Management by the Department of Library and Archives of Kuantan Singingi Regency was not optimal in terms of planning, organizing, directing and monitoring. The regional public library of Kuantan Singingi Regency has not met national standards. Inhibiting factors for the management of the Kuansing Library by the Kuantan Library and Archives Office in Singingi Regency are facilities and infrastructure, inadequate IT-based regulations and budget constraints. Keywords: Planning, Organizing, Direction, and Supervision.